A floating energy storage system based on fabric. (1st October 2018) - Klar, Robert; Steidl, Bernd; Aufleger, Markus
Abstract: This paper focuses on the theoretical investigation of the 'light' version of the Buoyant Energy (BE) storage concepts. Generally, BE transfers the pumped-storage hydropower key features to an offshore environment. The 'light' BE version is characterized by a lower water level of the surrounding water compared to the inner water level of the energy storage device. Therefore, it benefits from light construction material. Maybe the most lightweight construction method is the use of waterproof fabric material. First, the basic design aspects and ideal storage capacities of the original 'light' BE concept using rigid reservoirs is assessed. Second, a new design approach based on fabric is introduced. After describing and discussing its main components, the underlying equations are applied to form an exemplary energy storage device with 5 MWh capacity. Third, a design approach for increasing the energy storage capacity of airproof 'light' BE systems by added air compression to increase the pump-turbine head is presented. Fourth, floating stability aspects of 'light' BE devices are highlighted based on two exemplary box shaped designs. The results indicate that the ideas for using fabric as a construction material are promising and should be subject to further studies. Highlights: basic design aspects and storage capacities of 'Buoyant Energy' (BE) storage systems. Ideas for new BE systems based on fabric to decrease construction costs. Design approach for increasing the energy storage capacity by added air compression. Floating stability aspects of 'light' BE devices based on two exemplary box shaped designs.